A Novel CdSe/ZnS Quantum Dots Fluorescence Assay Based on Molecularly Imprinted Sensitive Membranes for Determination of Triazophos Residues in Cabbage and Apple - Hong, Sihui; She, Yongxin; Cao, Xiaolin; Wang, Miao; He, Yahui; Zheng, Lufei; Wang, Shanshan; Abd El-Aty, A. M.; Hacimüftüoglu, Ahmet; Yan, Mengmeng; Wang, Jing (Frontiers in Chemistry, 2019)
In the present study we have developed a direct competitive CdSe/ZnS quantum dots (QDs) fluorescence assay based on micro-array imprinted membranes for the determination of triazophos in cabbage and apple. The imprinted membranes were directly synthesized on the surface of a 96-well plate by thermal polymerization using triadimefon molecule as the dummy template. Under the optimal conditions, the assay showed an excellent linear response over the concentration ranges of 0.1-10000 μg L-1 with a good coefficient of determination (R2= 0.982). The sensitivity (IC50) and limit of detection (LOD, expressed as IC15) of the developed assay were 3.63 mg L-1 and 0.31 μg L-1, respectively. The applicability of the developed approach was tested for detecting triazophos in incurred samples. The method showed excellent recoveries (109.6 - 118.9%) and relative standard deviations (RSDs) between 9.9 - 19.5%. The obtained results correlated well with those obtained by LC-MS/MS (R2=0.9995). The competitive assay using CdSe/ZnS QDs as fluorescence-labeled probe showed a good sensitivity, steady, fast response, and excellent anti-interference ability compared to conventional fluorescence-quenching methods. At last, the feasibility of the proposed methodology was successfully applied for detection of triazophos in real samples.